PENGARUH KINERJA PENCIPTAAN NILAI, BAURAN PROMOSI, BUKTI JASA TERHADAP CITRA TAMAN REKREASI DALAM RANGKA PENGEMBANGAN CITRA JAKARTA SEBAGAI GREEN CITY - Sabar, Mudji (Universitas Pendidikan Indonesia, 2011)
This research was directed by the fact that Recreation Parks in Jakarta had not been optimising their performance so far. The total number of visitors of the Recreation Parks was not straightly in line with the total number of visitors to Jakarta. Tourists coming to Jakarta, both domestic and international, increased significantly year by year, whereas visitors of the Recreation Parks was fluctuating and decreasing since 2004. The main cause of this condition was the low performance of the corporate image of the Recreation Parks as perceived by the visitors. Accordingly, this research was focused on the efforts to increase the corporate image by analysing the attempts to upgrade the quality of value creation, promotion mix, and the evidence of service done by the Recreation Parks. The locus of this research was Jakarta the metropolitan city as one of the prime tourist destinations in Indonesia. By this choice, it is hoped that the result of this research would be applicable to all other destinations in Indonesia. The descriptive analysis was employed to uncover the performance of value creation, promotion mix, the evidence of service, and the corporate image of the Recreation Parks. The explanative analysis would statistically explain the relationship among variables, either simultaneuosly or individually, as well as identify the significant influence of each independent variable towards dependent variable. This research was aimed to search the visitors’ perception; therefore, the unit analysis of this research was consequently the visitors of the Recreation Parks in Jakarta. The charateristics of the chosen respondents were domestic visitors, adult, repeat visitors, and visitors who have ever visited all the 3 Recreation Parks in Jakarta. Data collection was done through observation, interview, and questioner addressed to 429 respondents. Data analysis was executed by path analysis. This research showed that the dominant influencing variable to increase the corporate image of the Recreation Parks was the evidence of service, mainly the physical evidence dimension. Moreover, it was identified that there were 2 solution factors in line with the concept of green tourism to be adopted to fasten the realization of Jakarta as a green city, ie green space and physical fasilities. In this case, the local government of Jakarta should widen the the area of green open space, improve the city’s drainage system, implement the city’s integrated garbage management, provide cheap and comfortable public transportation, execute emission control, diseminate soccial norms in line with the green tourism concept.